A young patient with atypical type-B Wolff–Parkinson–White syndrome accompanied by left ventricular dysfunction - Takahiro Takeuchi, MD (Journal of Arrhythmia, 2015)
A 15-year-old asymptomatic male patient presented with an electrocardiographic abnormality and left ventricular (LV) dysfunction (left ventricle ejection fraction of 40%) in a physical examination performed 2 years previously. LV dysfunction did not improve despite optimal medical therapy for dilated cardiomyopathy. Twelve-lead electrocardiography revealed a normal PR interval (138 ms) with a small delta-like wave in V2, but not a typical diagnostic wave that could be diagnosed as Wolff–Parkinson–White (WPW) syndrome by an electrocardiogram auto-analysis. Transthoracic echocardiography showed a remarkable asynchronous septal motion. An electrophysiological study was performed to exclude WPW syndrome. An accessory pathway (AP) was revealed on the lateral wall of the right ventricle, and radiofrequency catheter ablation was successfully performed to disconnect the AP. Thereafter, the dyssynchrony disappeared, and LV function improved. The intrinsic atrioventricular nodal conduction was very slow (A-H, 237 ms). The results of electrocardiogram auto-analysis could not be used to confirm the diagnosis of WPW syndrome because of the atypical delta wave. Conduction via the right lateral AP caused electrical dyssynchrony in the LV. This case suggests that atypical delta waves should be evaluated without depending on electrocardiographic auto-analyses in patients with LV dysfunction accompanied by dyssynchrony.